Monitoring w działaniach logistycznych na przykładzie transportu: Monitoring in logistic activities as an example of transport - Simiński, Przemysław; Simiński, Przemysław (Management and Administration Journal, 2021)
Operation of companies in economic reality is a constant attempt a looking for a balance of costs and revenues. Among the activities of logistics one of the key roles played by transportation. The article analyzes the potential benefits from the fact that monitoring systems.